تحسين كفاءة مراجل أنابيب اللهب من خلال تحديد نسبة الهواء الزائد الأمثل - حبيب محمود (Tishreen University, 2019)
في ظل الطلب العالمي المتزايد على الطاقة وارتفاع أسعار النفط أصبحت عمليات الحد من الهدر وتوفير الطاقة من خلال تحسين كفاءة مراجل البخار حاجة ملحة وضرورية، ومن الإجراءات المتبعة في تحسين كفاءة المراجل البحث عن النسبة المثلى للهواء الزائد، ولتحديد هذه النسبة ينبغي إجراء قياسات على أرض الواقع وفقا لظروف تشغيل كل مرجل.  ولهذا تم انجاز عدد من الاختبارات على مرجلين من مراجل أنابيب اللهب أحدها قديم والآخر حديث، وذلك بهدف إقلال مستوى الهواء الزائد إلى الحدود الدنيا مع المحافظة على الاحتراق كاملاً. وقد تم إنقاص الهواء الزائد من %79.5 إلى 36.3% للمرجل القديم، مما أدى إلى زيادة الكفاءة من 81.6% إلى 84.4%، وبالنسبة إلى المرجل الحديث فقد تم إنقاص الهواء من 46.7% إلى 33.3% وزيادة الكفاءة من 82.9% إلى 84.4% مع ازدياد طفيف بنسبة أكاسيد النيتروجين NOx المنبعثة. وهذا سيؤدي إلى توفير بالليرات السورية بمقداره 983920 ل. س. في السنة، وذلك حسب استهلاك الوقود السنوي للمرجلين. With the ever increasing world need for the power and high cost of fuel, the losses reducing and saving processes became very important through improving the boiler efficiency and determining optimum excess air ratio in real-time by performing measurements according to each boiler operation conditions. Therefore, a number of tests are performed on two boilers of fire tube boilers type, one of them is old and the other is modern to reduce the level of excess air to minimum term with maintaining complete combustion. The ratio of excess air has been reduced from 79.5 % to 36.3% for old boiler and its efficiency increased from 81.6 % to 84.4%. Also, for modern boiler the excess air has been reduced from 46.7 % to 33.3 % and the efficiency increased from 82.9% to 84.4% with little increased of nitrogen oxides NOx concentration of tow boilers. Also, the boiler efficiency improvements will allow earning 983920 S.P. in the year according to fuel consumption of tow boilers.